Anthelmintic Activity Of Melastoma Malabathricum Linn Leaves And Nigella Sativa Linn Seeds Extract (Journal of Engineering and Health Sciences, 2017)
In this study, the in vitro anthelmintic activity of the Melastoma malabathricum leaves and Nigella sativa seeds extract were tested. Extracts from both plants were prepared using methanol extraction method. Five concentrations of each set of individual Melastoma malabathricum extract, individual Nigella sativa extract and a 1:1 mixture of both plants extracts were prepared using adult motility assay. Eudrilus eugeniae was used in the experiment while albendazole 40 mg/ml and distilled water were used as positive and negative controls, respectively. The time required for paralysis and motility of the worms were recorded. The results were recorded in mean and were analyzed using the one-way ANOVA. The extracts of the Melastoma malabathricum leaves and Nigella sativa seeds were shown to possess significant anthelmintic effect. However, the effects were more prominent at higher concentrations of the extracts. Meanwhile, the combination of both plant extracts had demonstrated a better anthelmintic effect than their individual plant extract. This could be due to the presence of the synergistic effect from the combination of both extracts. Thus, combination of Melastoma malabathricum and Nigella sativa extracts has the potential to be used as natural remedy to treat parasitic infestation.